The Educational Implications of Hadiths on the Chapter on Honoring Parents and Maintaining Kinship Relations from Riyad Al- Salihin book and Their Contemporary Applications - As- Salami, Rafid Shalwan (Journal of Educational and Psychological Sciences, 2025)
This study aimed to derive the educational implications of the Hadiths on the Chapter on Honoring Parents and Maintaining Kinship Relations from Riyad AlSalihin book and their contemporary applications. A descriptive approach was used, based on the deductive approach.The study reached several conclusions, the most important of which are:1. Parents and kin have a significant impact on societal cohesion; the strength of the relationship between them leads to a cohesive internal fabric of society, which in turn strengthens the foundations of society as a whole.2. The interest of early scholars in education, both in documentation and practice, including Imam Muhyiddin al- Nawawi (may Allah have mercy on him). The study reached several recommendations, the most important of which are:1. Educating young men and women about to get married through associations and official platforms, through training courses and other means, about the Islamic educational ethics of the rights of parents and kinship.2- Disseminating research addressing the topic of honoring parents and maintaining family ties in Islamic education for reconciliation committees.
Keywords: Content; honoring parents; maintaining family ties; Riyad as- Salihin